Analysis of Factors that Make Tourists Interested in Visiting Batu City. - Ahmad Faidlal Rahman (Program Pendidikan Vokasi Universitas Brawijaya, 2016)
This research aims to determine the most dominant factors that make domestic tourists interested in visiting Batu city. The sample of this research is 100 domestic tourists. The sample was taken by using accidental sampling method. Data collection was done by distributing closed-ended questionnaires and using likert scale. The questionnaires were analyzed by using factor analysis of software SPSS 16. The findings show that factors which make domestic tourists interested in visiting Batu city are the atmosphere of townsquare at night (tourist attraction), the availability of communication facilities (amenity), transportation to tourist sites (accessibility), and tourism promotion activities (ancilliary services).